Indonesian English Pre-Service PPG Program: Students’ Perception - Nariza Ayu Pasha; Cindy Martina Marbun; Fidya Felinda Illahude; Ani Rizkiya; Iin Inawati (English Department - University of Sultan Ageng Tirtayasa, 2024)
With the development of technology, the system, strategies, and evaluation in teaching have also developed. Teachers are encouraged to enroll in a professional development program that can improve their qualities. In Indonesia, teachers who have been teaching in schools and prospective teachers who have just completed their education are recommended to enroll in a teacher certification program. For fresh graduates, the government provides a Pre-Service Teacher Professional Education program. Yet, studies investigating pre-service teachers' perceptions are scarcely reported. This study aims to explore the English pre-service teachers’ perception of joining the PPG program. The participants of this qualitative study were eight students who enrolled in PPG from various universities in Indonesia. Open-ended questionnaires and interviews were used to collect the data. This study used an interpretative inquiry method and Brenhonfebrenner's theory as a framework. The findings showed three factors influencing English pre-service teachers joining PPG: improving their quality and professionalism in teaching (self-improvement), being influenced by parents, lecturers, and colleagues (environmental support), and required by government regulations (government regulation). The implications of this research are expected to contribute to the government in considering policies related to the PPG program, as well as to teachers about continuing professional development.